2014
DOI: 10.1248/bpb.b13-00764
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effects of Cationic Hybrid Liposomes on the Hepatic Metastasis of Colon Carcinoma Along with Apoptosis <i>in Vivo</i>

Abstract: Therapeutic effects of cationic hybrid liposomes (HL) composed of 87 mol% dimyristoyl-phosphatidylcholine (DMPC), 5 mol% polyoxyethylene (21) dodecyl ether (C 12 (EO) 21 ) and 8 mol% O,O′-ditetradecanoyl-N-(α-trimethyl-ammonioacetyl) diethanolamine chloride (2C 14 ECl) on the metastasis of human colon carcinoma (HCT116) cells were examined in vivo. Cationic HL having a hydrodynamic diameter less than 150 nm were preserved for one month. Therapeutic effects were obtained in the hepatic metastasis mouse models o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…This inhibits liver metastasis and leads to decrease in the tumor volume. Importantly, hybrid liposomes (HLs) including PUFAs have demonstrated an inhibitory effect on the growth of tumor cells both in vitro and in vivo (Ichihara et al, 2014). Tanaka et al (2008) demonstrated that HLs enriched with n-3, n-6, and n-9 PUFAs inhibit the growth of tumor cells, including colon tumor (WiDr) cells in vitro .…”
Section: Pufas In Colorectal Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…This inhibits liver metastasis and leads to decrease in the tumor volume. Importantly, hybrid liposomes (HLs) including PUFAs have demonstrated an inhibitory effect on the growth of tumor cells both in vitro and in vivo (Ichihara et al, 2014). Tanaka et al (2008) demonstrated that HLs enriched with n-3, n-6, and n-9 PUFAs inhibit the growth of tumor cells, including colon tumor (WiDr) cells in vitro .…”
Section: Pufas In Colorectal Cancermentioning
confidence: 99%
“…They were then randomized for intravenous administration of liposomes, containing either L-α-dimyristoylphosphatidylcholine (DMPC) (136 mg/kg/d) or 50% molar DHA (65.7 mg/kg/d) and 50% molar DMPC. After 14 days of therapy, a significant improvement in median survival time and induction of apoptosis in liver metastases were observed (Ichihara et al, 2014). …”
Section: Pufas In Colorectal Cancermentioning
confidence: 99%
“…HL, composed of L-α-dimyristoylphosphatidylcholine (DMPC) and polyoxyethylene (23) dodecyl ethers (C 12 (EO) 23 ), are effective for inhibiting the growth of various cancer cells in vitro [6][7][8][9], in vivo [10,11] and clinical applications [12]. Recently, we have reported that HL composed of 90 mol% DMPC and 10 mol% C 12 (EO) 23 induced apoptosis in various cancer cells including NSCLC (A549, H460, H23 and H520) cells [9,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%